2017
DOI: 10.5114/reum.2017.68915
|View full text |Cite
|
Sign up to set email alerts
|

Three atypical manifestations of granulomatosis with polyangiitis: lateral medullary syndrome, anterior cheek mass and melting scleritis of eye

Abstract: Granulomatosis with polyangiitis (GPA, formerly Wegener granulomatosis) is a vasculitis with various organ involvement. There have been a few cases of CNS stroke and rare cases of lateral medullary infarction (LMI) as a manifestation of GPA. Also there have been reports of sinuses, nose and laryngeal masses mistakenly referred as carcinomas and subsequently GPA was diagnosed in their pathological reports. Another severe fulminant manifestation can be necrotizing scleritis leading to perforation of sclera. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Subcutaneous nodules associated with GPA have previously been reported in 1.1%-14.21% of patients with GPA ( 4 , 5 ). These nodules are reportedly located in the back, right armpit, and forehead of patients with GPA ( 5 ), whereas subcutaneous lesions in the anterior cheek have very rarely been reported ( 9 ). Shenavandeh et al reported the involvement of GPA in a patient who developed severe sinusitis, hearing loss, and a left cheek mass.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous nodules associated with GPA have previously been reported in 1.1%-14.21% of patients with GPA ( 4 , 5 ). These nodules are reportedly located in the back, right armpit, and forehead of patients with GPA ( 5 ), whereas subcutaneous lesions in the anterior cheek have very rarely been reported ( 9 ). Shenavandeh et al reported the involvement of GPA in a patient who developed severe sinusitis, hearing loss, and a left cheek mass.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 35.8% (34/95) of patients received just 1 cycle of RTX, leading to a positive response with disease remission in 84.3% (29/34), treatment failure in 14.7% (5/34), and disease relapse in 6.9% (2/29). The remaining 64.2% (61/95) of treated patients received between two to 15 cycles of RTX at intervals ranging from 1 to 6 months, with 18.0% (11/61) receiving one retreatment for disease relapse [48,61,68,70]. However, the rationale of designated treatment intervals and indications for retreatment in other reports were unclear.…”
Section: Uveitis Of Indeterminate Etiologymentioning
confidence: 99%
“…Atypical lesions are often the presenting feature in GPA, including mass lesion. This manifestation may present as parapharyngeal mass, parotid mass, sinonasal and maxillary sinus lesions, and subglottic paratracheal mass [66][67][68][69] . Typically, masses are associated with PR3-ANCA and occur at early stage of the disease, usually as part of a systemic disease (lung and kidney).…”
Section: Tumor-like Manifestationsmentioning
confidence: 99%